Phylogenetic analysis and secondary structure prediction for drought tolerant Cap binding proteins of plant species - BHATI, JYOTIKA; CHADUVULA, PAVAN K; KUMAR, SANJEEV; RAI, ANIL (The Indian Journal of Agricultural Sciences, 2013)
Cap binding proteins play an important role in improvement of drought tolerant varieties. Fifteen drought tolerantCap binding proteins from different plant species were phylogenetically analysed and their secondary structure werepredicted. On the rectangular cladogram (Mirabilis jalapa) was nearest to the origin and is placed separately with Ricinuscommunis forming separate cluster. The Cap binding proteins of Nicotiana tabacum were closely related with that ofSolanum tuberosum, showing their orthologous behaviour. Random coils constituted the maximum coverage along theentire length is a common trend in 14 drought tolerant proteins, irrespective of size and species family.